Suboptimal acclimation of photosynthesis to light in wheat canopies - Townsend, Alexandra J.; Retkute, Renata; Chinnathambi, Kannan; Randall, Jamie W.P.; Foulkes, John F; Carmo-Silva, Elizabete; Murchie, Erik H. (American Society of Plant Biologists, 2018)
Photosynthetic acclimation (photoacclimation) is the process whereby leaves alter their morphology and/or biochemistry to optimise photosynthetic efficiency and productivity according to long-term changes in the light environment. Three-dimensional (3D) architecture of plant canopies impose complex light dynamics, but the drivers for photoacclimation in such fluctuating environments are poorly understood. A technique for high-resolution 3D reconstruction was combined with ray tracing to simulate a daily time course of radiation profiles for architecturally contrasting field- grown wheat canopies. An empirical model of photoacclimation was adapted to predict the optimal distribution of photosynthesis according to the fluctuating light patterns throughout the canopies. Whilst the photoacclimation model output showed good correlation with field-measured gas exchange data at the top of the canopy, it predicted a lower optimal light saturated rate of photosynthesis (Pmax) at the base. Leaf Rubisco and protein content were consistent with the measured Pmax. We conclude that although the photosynthetic capacity of leaves is high enough to exploit brief periods of high light within the canopy (particularly towards the base), the frequency and duration of such sunflecks are too small to make acclimation a viable strategy in terms of carbon gain. This suboptimal acclimation renders a large portion of residual photosynthetic capacity unused, and reduces photosynthetic nitrogen use efficiency (PNUE) at thecanopy level with further implications for photosynthetic productivity. It is argued that(a) this represents an untapped source of photosynthetic potential and (b) canopy nitrogen could be lowered with no detriment to carbon gain or grain protein content.